1970
DOI: 10.1002/pol.1970.160080914
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of thin films. I. Acrylamide–N‐isopropylacrylamide copolymers in water

Abstract: The swelling curves of 6μ films of low conversion homopolymers and copolymers of acrylamide (AM) and N‐isopropylacrylamide (NIPAM) were obtained in water by an optical microscope technique. Poly(AM) swelled appreciably faster than poly(NIPAM) but there was no apparent correlation between overall swelling rate and copolymer composition. A 57/43 (mole %) AM–NIPAM copolymer swelled fastest. Sequence distribution calculations indicated that its backbone structure tended toward comonomer alternation, which might re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…This observation is consistent with the work of Chiklis and Grasshoff, which showed that AM is more reactive than NIPAM. 3 A more detailed analysis of copolymer microstructure is given in the discussion section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is consistent with the work of Chiklis and Grasshoff, which showed that AM is more reactive than NIPAM. 3 A more detailed analysis of copolymer microstructure is given in the discussion section.…”
Section: Resultsmentioning
confidence: 99%
“…Pendant drops were formed on the tip of a Teflon capillary with an outside diameter of 0.1 inch and inside diameter of 0.076 inch (Chromatographic Specialties Inc.). The pendant drop was enclosed in a sealed quartz cuvette (Hellma 330984, 10 ϫ 10 ϫ 30 mm, 3 Hellma), which was mounted in a Model 100-07 environmental chamber (Ramé Hart Inc.). The temperature control was Ϯ0.1°C.…”
Section: Dynamic Surface Tension Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the distribution of the different units inside the copolymer chains, we can only find information for the NIPA-AAm copolymerization. In that case, Chiklis and co-workers 17) have reported the following reactivity ratios: r NIPA = 0.5 and r AAm = 1.0. These values indicate that the heterogenity of the cotelomers, due to the composition drift with conversion, is rather low.…”
Section: Functional Oligomers and Co-oligomersmentioning
confidence: 95%
“…It is known that some water soluble polymers exhibit a lower critical solution temperature (LCST) in aqueous solution [1][2][3][4][5][6][7]. For example, poly-N-isopropylacrylamide (poly(NIPAAm)) has an LCST around 32°C [2][3][4][5].…”
mentioning
confidence: 99%